2014
DOI: 10.4103/1673-5374.141803
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative phosphorylated neurofilament protein M protects spinal cord against ischemia/reperfusion injury

Abstract: Previous studies have shown that neurofilament protein M expression is upregulated in the early stage of spinal cord ischemia/reperfusion injury, indicating that this protein may play a role in the injury process. In the present study, we compared protein expression in spinal cord tissue of rabbits after 25 minutes of ischemia followed by 0, 12, 24, or 48 hours of reperfusion with that of sham operated rabbits, using proteomic two-dimensional gel electrophoresis and mass spectrometry. In addition, the nerve re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 16 publications
0
2
0
Order By: Relevance
“…This was achieved through ROS (especially superoxide anion) capturing and increasing bioavailable nitric oxide (a potent vasodilator). Moreover, the endothelial nitric oxide synthase enzyme (eNOS), which is accountable for acting on arginine for NO biosynthesis, could be deactivated (uncoupled) through ROS-mediated arginase enzyme activation, which resulted in decreased blood flow and NO bioavailability [ 46 ]; therefore, the antioxidant capabilities of curcumin are thought to be the key reason for the improvement in uterine blood perfusion. This result agreed with the findings of El-Sherbiny et al [ 12 ], who reported that curcumin could improve testicular hemodynamics via its antioxidant effect during the non-breeding season in Baladi bucks.…”
Section: Discussionmentioning
confidence: 99%
“…This was achieved through ROS (especially superoxide anion) capturing and increasing bioavailable nitric oxide (a potent vasodilator). Moreover, the endothelial nitric oxide synthase enzyme (eNOS), which is accountable for acting on arginine for NO biosynthesis, could be deactivated (uncoupled) through ROS-mediated arginase enzyme activation, which resulted in decreased blood flow and NO bioavailability [ 46 ]; therefore, the antioxidant capabilities of curcumin are thought to be the key reason for the improvement in uterine blood perfusion. This result agreed with the findings of El-Sherbiny et al [ 12 ], who reported that curcumin could improve testicular hemodynamics via its antioxidant effect during the non-breeding season in Baladi bucks.…”
Section: Discussionmentioning
confidence: 99%
“…NF are the major neuron cytoskeletal protein, intervening in the increase in thickness of axons, involved in the conduction of nerve impulses [ 2 , 3 , 4 ], and with activity modulated by various physical and biochemical processes such as phosphorylation, glycosylation, nitration, oxidation, assembly–disassembly, or transport from the place of synthesis to the axonal level [ 2 , 3 ]. NFH, the subunit with the largest size, is ubiquitously found in neurons, with a maximum concentration at the axonal level, and its phosphorylated form (pNFH) is the most resistant to the action of various proteolytic enzymes—an important aspect in choosing it for an analysis as a marker of neuronal degradation [ 4 , 5 ]. Increased NF levels are directly proportional to the degree of neuronal injury and disease progression in various neurodegenerative diseases, such as multiple sclerosis, lateral amyotrophic sclerosis, spinal muscular atrophy, severe burns, Alzheimer’s disease, vascular or frontotemporal dementia, and Parkinson’s disease [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…IR is a common pathological process, which leads to the death of retinal ganglion cells (RGCs) and degeneration of the retina, resulting in loss of vision. At the cellular level, IR induces multi-cascade responses, including neuronal depolarization, calcium imbalance, nitric oxide, energy failure and increased glutamatergic stimulation, leading to oxidative stress ( 5 7 ).…”
Section: Introductionmentioning
confidence: 99%